The jungle books [large type] : featuring the complete and unabridged works the jungle book and the second jungle book - Kipling, Rudyard, 1865-1936 (Kennebec Large Print perennial favorites collection, 2009)
In the jungles of India, a pack of wolves discover a young boy. They name the boy Mowgli and protect him against dangers, including Shere Khan, the most savage tiger in the jungle. As Mowgli grows up, he learns the ways of the jungle from Bagheera the panther, the wise bear, Baloo, and other animals. Soon, he must decide whether to remain among beasts or embrace his own kind.